Cyber security in parallel and distributed computing : concepts, techniques, applications and case studies - Le, Dac-Nhuong, 1983-; Kumar, Raghvendra, 1987-; Mishra, Brojo Kishore, 1979-; Khari, Manju; Chatterjee, Jyotir Moy (Hoboken, NJ : John Wiley & Sons, Inc. ; Beverly, MA : Scrivener Publishing LLC, 2019)
'Covers privacy issue and challenges in data intensive cloud computing environment. Covers the concept of parallel and distributed computing technologies and their applications in real world settings. Offers data processing and security solutions Covers privacy issue and challenges in data intensive cloud computing environment. Includes the latest technologies that cover the major changes and advances of cyber security'--
Includes bibliographical references.
Online resource; title from digital title page (viewed on April 03, 2019).
Keywords: Computer security; Computer networks -- Security measures; Parallel processing (Electronic computers) -- Security measures; Electronic data processing -- Distributed processing -- Security measures; Electronic books